2020
DOI: 10.21203/rs.2.15898/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Educational Interventions on Oral Hygiene: A Systematic Review and Meta-Analysis

Abstract: Background: The objective of this study is to evaluate the effects of school based oral health interventions programs on students’ oral hygiene, in developing countries through systematic review and meta-analysis. Methods: Our investigation was conducted in electronic databases including MEDLINE Ovid), Embase Ovid, Scopus), Web of Science from 2000 to march 2018.The data were extracted based on a standard data collection form specific to observational studies, and entered into RevMan 2014. Inclusion criteria i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(51 reference statements)
1
0
0
Order By: Relevance
“…Thus, educational intervention can e ciently enhance oral health knowledge, and consequently promote oral health status of patients. Accordingly, the frequency of oral diseases and subsequent oral health-related costs would decrease (34). Consistent with the present results, Nesha et al (35) reported that only a small percentage of their study population had received information regarding the effect of periodontal disease on DM through their endocrinologist.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, educational intervention can e ciently enhance oral health knowledge, and consequently promote oral health status of patients. Accordingly, the frequency of oral diseases and subsequent oral health-related costs would decrease (34). Consistent with the present results, Nesha et al (35) reported that only a small percentage of their study population had received information regarding the effect of periodontal disease on DM through their endocrinologist.…”
Section: Discussionsupporting
confidence: 88%